THE INFLUENCE OF GULF WAR II ON IRAQ'S SOVEREIGNTY “AFTER THE INVASION OF KUWAIT IN 1990-2003” - Waruwu, David El Roy; Triwahana (CV. Fahr Publishing, 2024)
This research aims to find out 1) The background of Gulf War II, 2) The process of the Second Gulf War, and 3) The impact that occurred after the end of the Second Gulf War.This research uses literature research methods, and uses a descriptive approach that aims to describe the research accurately, factually, and coherently. The mechanism of this research starts from collecting sources (Heuristics), criticizing sources (Verification), interpreting or interpreting based on objectives, and doing historiography or historical writing. The results of the study concluded that, (1) The background of the Second Gulf War was due to Iraq's invasion of Kuwait, (2) The process of the Second Gulf War began when Iraq invaded Kuwait on August 2, 1990, and officially ended on February 28, 1991, (3) The impact of the Second Gulf War affected the sovereignty, economy and politics of Iraq.